Negative Attribution Bias and Anger After Traumatic Brain Injury. Issue 3 (May 2017) - Neumann, Dawn; Malec, James F.; Hammond, Flora M.
Abstract : Objectives: Negative attributions pertain to judgments of intent, hostility, and blame regarding others' behaviors. This study compared negative attributions made by people with and without traumatic brain injury (TBI) and examined the degree to which these negative attributions predicted angry ratings in response to situations. Setting: Outpatient rehabilitation hospital. Participants: Forty-six adults with moderate to severe TBI and 49 healthy controls. Design: Cross-sectional study using a quasi-experimental research design. Main Measures: In response to hypothetical scenarios, participants rated how irritated and angry they would be, and how intentional, hostile, and blameworthy they perceived characters' behaviors. There were 3 scenario types differentiated by the portrayal of characters' actions: benign, ambiguous, or hostile. All scenarios theoretically resulted in unpleasant outcomes for participants. Results: Participants with TBI had significantly higher ratings for feeling "irritated" and "angry" and attributions of "intent, " "hostility, " and "blame" compared with healthy controls for all scenario types. Negative attribution ratings accounted for 72.4% and 65.3% of the anger rating variance for participants with and without TBI, respectively. Conclusion: People with TBI may have negative attribution bias, in which they disproportionately judge the intent, hostility, and blameworthiness of others' behaviors. These attributions contributed to their ratings of feeling angry. This suggests that participants with TBI who have anger problems should be evaluated for this bias, and anger treatments should possibly aim to alter negative attributions. However, before implementing clinical practice changes, there is a need for replication with larger samples, and further investigation of the characteristics associated with negative attribution bias.